APPLYING GRAPHIC ORGANIZERS STRATEGYON GRADE TEN STUDENTS’ VOCABULARY ACQUISITION - Abdillah NA; Robiatul Adawiyah (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2017)
The purpose of this research was investigating of applying graphic organizers strategy on grade ten students’ vocabulary acquisition at SMA Martia Bhakti Bekasi, particularly to find out whether or not graphic organizers has significance effect on students’ vocabulary acquisition. The population of this research was the students on grade ten at SMA Martia Bhakti Bekasi, with the total number 225 students. Samples were gotten by adoptingcluster random sampling with the total number 60 students who is sitting on 2 classes. One of classes was assigned to an experimental group, whose students were taught using the GO strategy with five specific features of vocabulary items, they are definition, synonym, antonym, example, and using it in an example sentences. While the other class was assigned to be control group, whose students were taught with the same vocabulary items using conventional strategy. The research methodology used quasi experiment method and the research design adopted post test only control group design. After gave the treatment to the experiment and control groups, the post testwas conductedformeasuringeffectivenessof the treatment, numbering 30 items. At the end of the session, the data was analyzed using SPSS v. 21. The researcher used One-Way ANOVA for analysis. The result showed that the F observed is higher than F table (4.00, come from significant level 0.05 and df= 1/58). It means that graphic organizers strategy has significant effect on students’ vocabulary acquisition.